Role of Ultrasound in the Diagnosis of Superficial Lymphadenopathy of the Neck - Zakirkhodjaevna Pulatova, Iroda; Mamasalievna Mamadalieva, Yashnar; Erkinovna Shamsieva, Lorida (International Journal of Psychosocial Rehabilitation, 2020)
This article presents the results of ultrasound in B-mode and color Doppler mapping with spectral characteristics of 53 patients with head and neck diseases with metastatic processes in regional lymph nodes. The described ultrasound criteria made it possible to assess the nature and degree of damage to the neck lymph nodes, which significantly influenced the choice of further treatment tactics.